Association of fall history with the Timed Up and Go test score and the dual task cost: A cross‐sectional study among independent community‐dwelling older adults. Issue 8 (21st May 2018) - Asai, Tsuyoshi; Oshima, Kensuke; Fukumoto, Yoshihiro; Yonezawa, Yuri; Matsuo, Asuka; Misu, Shogo
Abstract : Aim: To investigate the associations between fall history and the Timed Up and Go (TUG) test (single‐TUG test), TUG test while counting aloud backwards from 100 (dual‐TUG test) and the dual‐task cost (DTC) among independent community‐dwelling older adults. Methods: This cross‐sectional study included 537 older adults who lived independently in the community. Data on fall history in the previous year were obtained by self‐administrated questionnaire. The single‐ and dual‐TUG tests were carried out, and the DTC value was computed from these results. Associations between fall history and these TUG‐related values were analyzed using multivariate logistic regression models. The participants were divided into fall risk groups using the cut‐off values of those significantly associated with falling, and the odds ratios (OR) were computed. Results: Slower single‐TUG test scores and lower DTC values were significantly associated with fall history after adjusting for potential confounders (single‐TUG test score: OR 1.133, 95% CI 1.029–1.249; DTC value: OR 0.984, 95% CI 0.968–0.998). Older adults with slower single‐TUG test scores and lower DTC values reported a fall history more often than those in other categories (OR compared with the lower‐risk single‐TUG and lower‐risk DTC groups: 3.474, 95% CI 1.881–6.570). Conclusions: Slower single‐TUG test scores and lower DTC values are associated with fall history among independent community‐dwelling older adults. To some extent, dual task performance might provide added value for fall assessment, compared with administering the TUG test alone.Geriatr Gerontol Int 2018; 18: 1189–1193 .